Milk-borne diseases through the lens of one health - Kapoor, Sunandini; Goel, Akhil Dhanesh; Jain, Vidhi (Frontiers in Microbiology, 2023)
Reviewing ‘zoonotic diseases’ classically brings to mind human infections contracted in close association with animals, where outdoor occupations and afforested lands usually play a key role in the epidemiological triad. However, there is a very common, yet overlooked route of infection where humans may not come in direct contact with animals or implicated environments. Milk-borne diseases are a unique set of infections affecting all age groups and occupational categories of humans, causing 4% of all the foodborne diseases in the world. The infection reservoir may lie with milch animals and associated enzootic cycles, and the infectious agent is freely secreted into the animal’s milk. Commercial pooling and processing of milk create unique environmental challenges, where lapses in quality control could introduce infective agents during downstream processing and distribution. The infectious agent is finally brought to the doorstep of both rural and urban households through such animal products. The domestic hygiene of the household finally determines human infections. One health approach can target preventive measures like immunization in animals, pasteurization and stringent quality control during the commercial processing of milk, and finally, hygienic practices at the level of the consumer, to reduce the burden of milk-borne diseases. This review hopes to draw the attention of policymakers to this unique route of infection, because it can be easily regulated with cost-effective interventions, to ensure the safety of this precious food product, permeating the life and livelihood of humans from all walks of life.